EFFECTS OF DIETARY MANNAN OLIGOSACCHARIDE ON MUSCLE PROTEIN, INTESTINAL MORPHOLOGY AND BLOOD CELL COUNT OF CLOWNFISH, AMPHIPRION OCELLARIS - Hoang, Do Huu; Lu, Hoang Duc; Ky, Pham Xuan; Tram, Dang Tran Tu; Kim Bich, Nguyen Thi; Lam, Ho Son; Huynh, Tran van; Ha, Dao Viet; Hong, Nguyen Thu; Vi, Phan Bao (Vietnam Journal of Marine Science and Technology, 2014)
Clownfish, Amphiprion ocellaris (2.4 cm) were cultured in recirculation system, volume of 50 L and density of 20 fish per tank. Six levels of mannan oligosacharide (MOS), including 0.05%, 0.10%, 0.15%, 0.20%, 0.25% and 0.30% were supplemented to the control diet and fed to the fishfor 10 weeks. Collected data included ratio of internal and external intestinal perimeter of the gut (PR), muscle protein content and total blood cell count. Result showed that the PR was highest in the fish fed by 0.1 and 0.15% MOS and lowest in two groups of fish fed by control and 0.3% MOS in their diet (P <0.05). After 4 weeks of diet feeding, protein content in the fish among the treatments ranged from 12.85%P to 15.53%P. Those values seemed to increase at week 10 in compared to week 4, however; there was no significant difference in protein content among the treatments at either week 4 or week 10 measurements. Total blood cell count of fish at week 10 were highest in the group of fish fed on 0.05% MOS (26.22×105 ± 2.80×105 cells/mm3), followed by the groups of fish fed 0.25% and 0.1% with blood count being 21.54×105 ± 3.65×105 cells/mm3 and 20.73×105 ± 7.88 ×105 cells/mm3. Respectively the lowest blood cell count was in the fish fed by 0.15% MOS MOS (11,02×105 ± 2,00 ×105 cells /mm3). There was a statistically significant difference between blood cell count of fish fed by 0.05% MOS in compared to fish fed by control diet and 0.15% MOS (P < 0,05).